Representation of the laser self-mixing effect in an acoustic signal - Wojaczek, Dorota; Pliński, Edward; Dobrucki, Andrzej (Archives of Acoustics, 2006)
The goal of the work is to check the possibility of observing the optical phenomena in thegas laser plasma using a microphone. An RF excited slab-waveguide carbon dioxide laser isused in the experiment. The investigations are performed on a three mirror resonator structure.An outside mirror is fixed to a vibration exciter to obtain a returnig wave to the laser resonator.In that way a self-mixing phenomenon is observed with the optical detector. The response ofthe laser plasma changes is detected as an acoustic signal. The results of the investigations canbe useful for controlling the laser tuning.